Method for manufacturing outer shell of scooter
Through the multi-layer composite material process, combined with substrate and reinforcement materials, the shortcomings in the outer shell of the scooter in terms of strength, durability and impact resistance are solved, efficient and economical production is achieved, and the performance and service life of the outer shell are improved.
Patent Information
- Application Number
- CN202411920121.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
The existing scooter outer shell materials have shortcomings in strength, durability, impact resistance and lightweight, and the production process is not efficient.
Using a multi-layer composite material process, by selecting suitable substrates (such as polypropylene or polyester) and reinforcement materials (such as glass fiber or carbon fiber), combined with resin materials, pretreatment, hot pressing and preparation of multi-layer composite structures, an outer shell with high strength, impact resistance and lightweight properties are formed.
It significantly improves the mechanical properties and durability of the outer shell of the scooter, reduces production costs, improves production efficiency, and enhances the ultraviolet and corrosion resistance of the outer shell.
Smart Images

Figure CN119704751A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a mobility scooter technology, and more specifically, to a method for manufacturing an outer shell of a mobility scooter. Background Art
[0002] With the acceleration of urbanization, mobility scooters, as a convenient means of personal travel, have been widely used in short-distance travel in cities. The strength, lightness and weather resistance of the outer shell of mobility scooters are crucial to their safety and service life. Traditional mobility scooters are mostly made of metal or plastic materials, but these materials have certain deficiencies in strength, durability, impact resistance and lightness, and are not easy to mass produce. Therefore, how to improve the performance of the outer shell of mobility scooters while ensuring the efficiency and stability of the production process has become a difficulty in the development of related technologies.
[0003] The object of the present invention is to provide a method for manufacturing an outer shell of a mobility scooter, which, through a multi-layer composite material process, enables the outer shell to have high strength, good impact resistance and lightweight characteristics, while being able to reduce production costs and improve production efficiency. Summary of the invention
[0004] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for manufacturing an outer shell of a mobility scooter having high strength, good impact resistance and light weight.
[0005] To achieve the above object, the present invention provides the following technical solution: a method for manufacturing an outer shell of a mobility scooter, comprising the following steps:
[0006] S1. Preparation of outer shell substrate: First, according to the design requirements of the mobility scooter, select a suitable substrate: polypropylene or polyester or enhanced polyester material; and cut it into a predetermined outer shell mold shape;
[0007] S2. Pretreatment of reinforcing materials: According to the strength requirements of the outer shell, select suitable reinforcing materials: glass fiber, carbon fiber or natural fiber; pretreat the prepared glass fiber, carbon fiber or natural fiber, and use acid washing and surface coating technology to make its surface have good adhesion properties and enhance the bonding strength with the resin material; the specific steps are: soak the fiber material in a 5%-10% hydrochloric acid solution for 30 minutes, then wash it with deionized water, and apply a layer of reinforcing agent after drying to ensure that the bonding strength between the resin and the fiber meets the preset requirements;
[0008] S3. Preparation of reinforcing layer: The reinforcing layer is prepared by adding resin material: epoxy resin or polyurethane resin to the reinforcing material; this reinforcing layer is usually presented in the form of fabric or cloth, and has good mechanical properties and impact resistance; the formula used is: 50-60% epoxy resin, 30-40% glass fiber, 5-10% curing agent, and 5-10% solvent;
[0009] S4. Mould design and preparation: Design and manufacture a mould that meets the requirements according to the shape and structure of the outer shell of the mobility scooter. The mould material is made of aluminium alloy to ensure good thermal conductivity and surface smoothness. The mould size and shape are optimized according to the body structure to ensure that the produced shell meets the various specifications of the body.
[0010] S5. Preparation of a multi-layer composite structure: The reinforcement layer and the outer shell substrate are composited by a hot pressing process; at this time, an intermediate isolation layer can be added as needed to enhance the toughness, tensile strength and compressive strength of the outer shell;
[0011] S6. Treatment of the exterior layer: In order to improve the appearance and durability of the outer shell of the mobility scooter, a layer of UV-resistant and corrosion-resistant exterior protective layer is applied to the outside of the composite structure; this protective layer can be coated with UV curing paint or polyurethane paint, and the thickness is generally controlled at 0.5-1mm; the formula of the paint used is: polyurethane resin 60-70%, ultraviolet absorber 5-10%, curing agent 10-15%, solvent 10-15%;
[0012] Through UV curing or heat curing, the exterior layer has good adhesion and weather resistance, ensuring that the surface of the outer shell of the mobility scooter can resist erosion by sunlight, rain and other environmental factors;
[0013] S7. Reinforcement of the inner lining layer: In order to further improve the impact resistance and scratch resistance of the outer shell, a special inner lining layer can be coated inside the outer shell; the inner lining layer is generally made of high-strength polyurethane material, and the formula is: polyurethane resin 50-60%, nano filler 10-20%, curing agent 5-10%, solvent 10-15%;
[0014] S8, curing treatment: put the treated outer shell into an oven for curing treatment; the curing temperature is 80℃-120℃, and the curing time is 12-16 hours to ensure full curing and make the outer shell have the best mechanical properties and thermal stability;
[0015] S9, outer shell molding and trimming: The solidified outer shell is cooled, and the outer shell is initially molded; at this time, the outer shell needs to be fine-finished, polished and painted to ensure a smooth, defect-free and flawless appearance; during the trimming process, a fine grinding tool is used to polish the outer shell surface and trim the edge to ensure that the geometric size and shape of the outer shell meet the design requirements;
[0016] S10, Testing and Quality Inspection: In order to ensure the quality of the outer shell of the mobility scooter, strict testing and quality inspection must be carried out. The testing contents include:
[0017] S101, Strength test: Use tensile test, compression test and impact test methods to test the tensile strength, compressive strength and impact strength of the outer shell to ensure that it meets the use requirements;
[0018] S102, temperature resistance test: put the outer shell into a high temperature environment for testing, to detect its tolerance under high temperature conditions, to ensure that it can still maintain stability under extreme temperature conditions;
[0019] S103, corrosion resistance test: salt spray test and acid-base test are used to detect the corrosion resistance of the outer shell;
[0020] S104, Appearance inspection: Conduct a comprehensive inspection on the outer shell surface to ensure there are no bubbles or cracks;
[0021] S11. Finished product packaging and delivery: After passing the above tests, the outer shell will enter the packaging stage; according to customer needs, appropriate packaging treatment will be carried out to ensure that it is not damaged during transportation.
[0022] The present invention is further configured as follows: in said S5, the specific compounding process includes:
[0023] Preheating: Lay the base material and the reinforcement layer in the mold according to the predetermined direction and density, and preheat them. The temperature is controlled at 120℃-130℃ to achieve a better bonding effect during the subsequent compounding.
[0024] Hot pressing: The heated substrate and reinforcement layer are hot pressed into shape. The molding process temperature is set at 150℃-180℃, the pressure is 8-12MPa, and the holding time is 20-30min to ensure that the composite layer is uniform and tight.
[0025] The present invention is further configured as follows: in S5, the middle isolation layer is composited by an inorganic thermal insulation material and an organic foam material, the mass ratio of the composite material is 60:40, and the thickness of the thermal insulation layer is 0.5 mm to 1 mm, ensuring that the outer shell has good thermal insulation performance.
[0026] The present invention is further configured as follows: in S101, the strength test includes the following steps:
[0027] S101-1. Tensile test:
[0028] S101-11. Cut a tensile test piece that meets the standards from the outer shell material; the test piece is usually in the shape of a long strip with a width of 20 mm and a thickness selected according to the actual thickness of the outer shell. The length is greater than 100 mm, and the surface of the test piece needs to be flat and smooth to ensure that there are no defects;
[0029] S101-12. Install the outer shell specimen in the fixture of the tensile testing machine, ensuring that the clamping position is firm and the two ends are symmetrical;
[0030] S101-13. Start the tensile testing machine and apply tensile force. During the stretching process, monitor and record the stress and strain changes of the outer shell; the loading rate is controlled between 1-5 mm / min;
[0031] S101-14. During the stretching process, record the breaking point of the outer shell; at this time, the test machine automatically stops and records the maximum tensile force and breaking strain;
[0032] S101-15. If the maximum tensile force of the outer shell specimen is higher than the tensile strength required by the design, the tensile test is qualified and the compression test is carried out in S101-2;
[0033] S101-16. If the maximum tensile force value of the outer shell specimen is lower than the tensile strength required by the design, the specimen is re-cut from the outer shell material away from the first cutting position, and the tensile test is re-performed. If the maximum tensile force value of the new outer shell specimen is higher than the tensile strength required by the design, the tensile test is qualified, and the compression test is performed in S101-2; if it is still lower than the tensile strength required by the design, the tensile test is unqualified, and the operator makes corresponding adjustments to the manufacturing method based on the test results;
[0034] S101-2, compression test:
[0035] S101-21. Cut a round or square specimen suitable for compression test from the same piece of outer shell material that has passed the outer shell tensile test. The size requirement is that the side length or diameter is 50mm and the thickness is 1.5 times the actual thickness of the outer shell. Ensure that the surface of the specimen is flat and free of defects;
[0036] S101-22. Place the specimen on the compression tester's lower platform, ensuring that the specimen is centered and stable;
[0037] S101-23. Apply compression force slowly, and control the compression rate at 1-2 mm / min. When the specimen begins to be subjected to pressure, record the applied compression force and the deformation of the specimen.
[0038] S101-24. Continue to apply the compressive force until the specimen begins to produce obvious permanent deformation or rupture, and record the maximum compressive force and its corresponding deformation;
[0039] S101-25. If the outer shell specimen does not break within the set load range and recovers well after compression, the compression test is qualified and the impact test is carried out in S101-3.
[0040] S101-26, if the outer shell specimen is broken within the set load range and has poor recovery after compression, the specimen is re-cut from the outer shell material away from the first cutting position, and the compression test is re-performed. If the new outer shell specimen does not break within the set load range and has good recovery after compression, the compression test is qualified, and the process goes to S101-3 for impact test; if it still breaks within the set load range and has poor recovery after compression, the compression test is unqualified, and the operator makes corresponding adjustments to the manufacturing method based on the test results;
[0041] S101-3, impact test:
[0042] S101-31. Cut standard-sized impact specimens from the same piece of outer shell material that has passed the outer shell tensile test and compression test. The size requirement is a square specimen of 10×10 cm. The surface of the specimen should be free of any cracks or defects to ensure the accuracy of the impact test;
[0043] S101-32. Fix the specimen on the support table of the impact tester to ensure its stable position;
[0044] S101-33. Start the impact tester and make the standard impact hammer hit the test piece at a set speed. Adjust the impact energy according to the design requirements.
[0045] S101-34. Record the cracks or damage of the test piece after impact and evaluate the impact resistance of the outer shell material;
[0046] S101-35. If the specimen has no cracks or breaks, the impact test is qualified;
[0047] S101-36. If cracks or breaks appear on the specimen, re-cut the specimen from the outer shell material away from the first cutting position and re-perform the impact test. If the new outer shell specimen does not have cracks or breaks, the impact test is qualified; if cracks or breaks still appear, the impact test is unqualified. The operator shall make corresponding adjustments to the manufacturing method based on the test results.
[0048] The present invention is further configured as follows: in S2, the length of the reinforcing material is 10-15 mm, and the diameter is 5-10 μm.
[0049] The beneficial effects of the present invention are:
[0050] 1. Compared with the prior art, the manufacturing method of the outer shell of the scooter of the present invention significantly improves the mechanical properties and durability of the outer shell through the design and processing of the multi-layer composite material. First, in terms of substrate selection, the application of materials such as polypropylene or polyester has good processability, corrosion resistance and light weight, which can effectively reduce the weight of the vehicle body while maintaining a certain strength. The use of reinforcing materials, such as glass fiber or carbon fiber, can greatly improve the tensile strength, compressive strength and impact resistance of the outer shell, enhance the service life of the outer shell, and reduce the probability of damage. In addition, the composite process of resin and reinforcing materials not only ensures the high strength of the outer shell, but also can effectively improve the impact resistance and ensure the safety during use. Through precise mold design and hot pressing molding process, the dimensional accuracy of the outer shell is ensured, the scrap rate is reduced, thereby reducing the production cost. The optimization of the overall production process combines the processing of the reinforcing layer, the appearance layer and the lining layer, so that the outer shell has a high environmental adaptability such as UV resistance and corrosion resistance, ensures the long-term stability of the outer shell of the scooter, improves production efficiency, and further promotes the wide application of the manufacturing method.
[0051] 2. The manufacturing method of the outer shell of the mobility scooter of the present invention optimizes the preheating and hot pressing process during the composite process, which significantly improves the bonding and mechanical properties of the composite material. By controlling the temperature and pressure, the reinforcing layer and the substrate can achieve a uniform hot pressing effect in the mold to form a dense, high-strength composite layer. Specifically, the preheating stage uses a heating temperature of 120°C-130°C to ensure that the reinforcing layer and the substrate can fully exert their bonding force during the composite process, avoiding the problem of poor bonding or insufficient mechanical properties due to insufficient temperature. The hot pressing process further strengthens the compactness of the composite layer, making the bond between the reinforcing layer and the substrate more firm, which not only improves the tensile strength and impact resistance of the outer shell, but also greatly improves the overall stability of the outer shell. This improvement makes the error in the manufacturing process smaller and the mechanical properties of the finished outer shell are more uniform and reliable. In addition, the improvement of the composite process also shortens the production cycle to a certain extent, improves production efficiency, and thus effectively reduces production costs.
[0052] 3. In the present invention, by setting an intermediate isolation layer, the performance of the outer shell is further improved, especially in terms of heat insulation. The inorganic heat insulation material can effectively block the change of the external temperature, prevent the temperature inside the vehicle from being too high or too low, and ensure the stability of the vehicle environment. The addition of organic foam material can not only further enhance the heat insulation performance, but also reduce the weight of the outer shell, which is helpful to achieve the lightweight design of the vehicle. The use of this composite material not only improves the comfort of the outer shell, but also increases the impact resistance of the vehicle body, avoiding excessive damage during collision. The thickness of the intermediate isolation layer is in the range of 0.5mm to 1mm, which can effectively play a heat insulation role without affecting the strength and stability of the overall structure.
[0053] 4. The present invention ensures the reliability and stability of the outer shell under various conditions such as tension, compression and impact. Through precise tension, compression and impact tests, the mechanical properties of the outer shell can be comprehensively evaluated, especially the performance under high-intensity load. The tension test can test the tensile strength to ensure that the outer shell will not break or damage during the tension process, and ensure that it can withstand a large tensile force in actual use; the compression test tests the compressive strength of the outer shell, evaluates its deformation under the action of compression force, and ensures that the outer shell will not have excessive permanent deformation or rupture when subjected to external pressure; the impact test further verifies the impact resistance of the outer shell, ensuring that the outer shell can effectively absorb energy when encountering external impact, avoiding damage to the vehicle body structure; through these strict quality controls, not only the high strength and impact resistance of the outer shell are ensured, but also the optimization of the manufacturing method can be achieved, the production efficiency can be improved, and at the same time, the waste and cost caused by unqualified products are reduced, and ultimately the manufacturing process is made more efficient. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 The present invention is a flow chart of a method for manufacturing an outer shell of a mobility scooter.
[0055] Figure 2 It is a structural diagram of the walking vehicle of the present invention. DETAILED DESCRIPTION
[0056] Reference Figure 1-2 The manufacturing method of the outer shell of the mobility scooter of the present invention is further described in an embodiment.
[0057] For ease of explanation, spatial relative terms such as "upper", "lower", "left", "right" and the like are used in the embodiments to illustrate the relationship of one element or feature shown in the figure relative to another element or feature. It should be understood that, in addition to the orientation shown in the figure, the spatial terms are intended to include different orientations of the device in use or operation. For example, if the device in the figure is inverted, the element described as being "under" other elements or features will be positioned "on" other elements or features. Therefore, the exemplary term "under" can include both upper and lower orientations. The device can be positioned in other ways (rotated 90 degrees or in other orientations), and the spatial relative descriptions used here can be interpreted accordingly.
[0058] Furthermore, relational terms such as “first” and “second” and the like are merely used to distinguish one component from another having the same name, but do not necessarily require or imply any such actual relationship or order between these components.
[0059] Figure 1 to Figure 2 The manufacturing method of the outer shell of a mobility scooter shown in the figure comprises the following steps:
[0060] S1. Preparation of outer shell substrate: First, according to the design requirements of the mobility scooter, select a suitable substrate: polypropylene or polyester or enhanced polyester material; and cut it into a predetermined outer shell mold shape;
[0061] S2. Pretreatment of reinforcing materials: According to the strength requirements of the outer shell, select suitable reinforcing materials: glass fiber, carbon fiber or natural fiber; pretreat the prepared glass fiber, carbon fiber or natural fiber, and use acid washing and surface coating technology to make its surface have good adhesion properties and enhance the bonding strength with the resin material; the specific steps are: soak the fiber material in a 5%-10% hydrochloric acid solution for 30 minutes, then wash it with deionized water, and apply a layer of reinforcing agent after drying to ensure that the bonding strength between the resin and the fiber meets the preset requirements;
[0062] S3. Preparation of reinforcing layer: The reinforcing layer is prepared by adding resin material: epoxy resin or polyurethane resin to the reinforcing material; this reinforcing layer is usually presented in the form of fabric or cloth, and has good mechanical properties and impact resistance; the formula used is: 50-60% epoxy resin, 30-40% glass fiber, 5-10% curing agent, and 5-10% solvent;
[0063] S4. Mould design and preparation: Design and manufacture a mould that meets the requirements according to the shape and structure of the outer shell of the mobility scooter. The mould material is made of aluminium alloy to ensure good thermal conductivity and surface smoothness. The mould size and shape are optimized according to the body structure to ensure that the produced shell meets the various specifications of the body.
[0064] S5. Preparation of a multi-layer composite structure: The reinforcement layer and the outer shell substrate are composited by a hot pressing process; at this time, an intermediate isolation layer can be added as needed to enhance the toughness, tensile strength and compressive strength of the outer shell;
[0065] S6. Treatment of the exterior layer: In order to improve the appearance and durability of the outer shell of the mobility scooter, a layer of UV-resistant and corrosion-resistant exterior protective layer is applied to the outside of the composite structure; this protective layer can be coated with UV curing paint or polyurethane paint, and the thickness is generally controlled at 0.5-1mm; the formula of the paint used is: polyurethane resin 60-70%, ultraviolet absorber 5-10%, curing agent 10-15%, solvent 10-15%;
[0066] Through UV curing or heat curing, the exterior layer has good adhesion and weather resistance, ensuring that the surface of the outer shell of the mobility scooter can resist erosion by sunlight, rain and other environmental factors;
[0067] S7. Reinforcement of the inner lining layer: In order to further improve the impact resistance and scratch resistance of the outer shell, a special inner lining layer can be coated inside the outer shell; the inner lining layer is generally made of high-strength polyurethane material, and the formula is: polyurethane resin 50-60%, nano filler 10-20%, curing agent 5-10%, solvent 10-15%;
[0068] S8, curing treatment: put the treated outer shell into an oven for curing treatment; the curing temperature is 80℃-120℃, and the curing time is 12-16 hours to ensure full curing and make the outer shell have the best mechanical properties and thermal stability;
[0069] S9, outer shell molding and trimming: The solidified outer shell is cooled, and the outer shell is initially molded; at this time, the outer shell needs to be fine-finished, polished and painted to ensure a smooth, defect-free and flawless appearance; during the trimming process, a fine grinding tool is used to polish the outer shell surface and trim the edge to ensure that the geometric size and shape of the outer shell meet the design requirements;
[0070] S10, Testing and Quality Inspection: In order to ensure the quality of the outer shell of the mobility scooter, strict testing and quality inspection must be carried out. The testing contents include:
[0071] S101, Strength test: Use tensile test, compression test and impact test methods to test the tensile strength, compressive strength and impact strength of the outer shell to ensure that it meets the use requirements;
[0072] S102, temperature resistance test: put the outer shell into a high temperature environment for testing, to detect its tolerance under high temperature conditions, to ensure that it can still maintain stability under extreme temperature conditions;
[0073] S103, corrosion resistance test: salt spray test and acid-base test are used to detect the corrosion resistance of the outer shell;
[0074] S104, Appearance inspection: Conduct a comprehensive inspection on the outer shell surface to ensure there are no bubbles or cracks;
[0075] S11. Finished product packaging and delivery: After passing the above tests, the outer shell will enter the packaging stage; according to customer needs, appropriate packaging treatment will be carried out to ensure that it is not damaged during transportation;
[0076] The manufacturing method of the outer shell of a mobility scooter of the present invention significantly improves the mechanical properties and durability of the outer shell through the design and processing of a multi-layer composite material. First, in terms of substrate selection, the use of materials such as polypropylene or polyester has good processability, corrosion resistance and light weight, which can effectively reduce the weight of the vehicle body while maintaining a certain strength. The use of reinforcing materials, such as glass fiber or carbon fiber, can greatly improve the tensile strength, compressive strength and impact resistance of the outer shell, enhance the service life of the outer shell, and reduce the probability of damage. In addition, the composite process of resin and reinforcing materials not only ensures the high strength of the outer shell, but also can effectively improve the impact resistance and ensure safety during use. Through precise mold design and hot pressing molding process, the dimensional accuracy of the outer shell is ensured, the scrap rate is reduced, thereby reducing the production cost. The optimization of the overall production process combines the processing of the reinforcing layer, the appearance layer and the lining layer, so that the outer shell has a high environmental adaptability such as UV resistance and corrosion resistance, ensures the long-term stability of the outer shell of the mobility scooter, improves production efficiency, and further promotes the wide application of the manufacturing method.
[0077] In S5, the specific compounding process includes:
[0078] Preheating: Lay the base material and the reinforcement layer in the mold according to the predetermined direction and density, and preheat them. The temperature is controlled at 120℃-130℃ to achieve a better bonding effect during the subsequent compounding.
[0079] Hot pressing: The heated substrate and reinforcement layer are hot pressed into shape. The molding process temperature is set at 150℃-180℃, the pressure is 8-12MPa, and the holding time is 20-30min to ensure that the composite layer is uniform and tight;
[0080] The optimization of preheating and hot pressing process in the composite process significantly improved the bonding and mechanical properties of the composite material. By controlling the temperature and pressure, the reinforcement layer and the substrate can achieve a uniform hot pressing effect in the mold to form a dense and high-strength composite layer. Specifically, the preheating stage uses a heating temperature of 120℃-130℃ to ensure that the reinforcement layer and the substrate can fully exert their bonding force during the composite process, avoiding the problem of poor bonding or insufficient mechanical properties caused by insufficient temperature. The hot pressing process further strengthens the compactness of the composite layer, making the bond between the reinforcement layer and the substrate more firm, which not only improves the tensile strength and impact resistance of the outer shell, but also greatly improves the overall stability of the outer shell. This improvement makes the error in the manufacturing process smaller and the mechanical properties of the finished outer shell are more uniform and reliable. In addition, the improvement of the composite process has also shortened the production cycle to a certain extent, improved production efficiency, and effectively reduced production costs.
[0081] In S5, the middle isolation layer is composed of an inorganic heat-insulating material and an organic foam material, the mass ratio of the composite material is 60:40, and the thickness of the heat-insulating layer is 0.5 mm to 1 mm, so as to ensure that the outer shell has good heat-insulating performance;
[0082] The performance of the outer shell is further improved, especially in terms of heat insulation. The inorganic heat insulation material can effectively block the change of the external temperature, prevent the temperature inside the vehicle from being too high or too low, and ensure the stability of the vehicle environment. The addition of organic foam material can not only further enhance the heat insulation performance, but also reduce the weight of the outer shell, which helps to achieve the lightweight design of the vehicle. The use of this composite material not only improves the comfort of the outer shell, but also increases the impact resistance of the vehicle body to avoid excessive damage during collision. The thickness of the middle isolation layer is in the range of 0.5mm to 1mm, which can effectively play a heat insulation role without affecting the strength and stability of the overall structure. This structural design enables the outer shell of the vehicle to have excellent performance while maintaining a low production cost and improving production efficiency.
[0083] In S101, the strength test includes the following steps:
[0084] S101-1. Tensile test:
[0085] S101-11. Cut a tensile test piece that meets the standards from the outer shell material; the test piece is usually in the shape of a long strip with a width of 20 mm and a thickness selected according to the actual thickness of the outer shell. The length is greater than 100 mm, and the surface of the test piece needs to be flat and smooth to ensure that there are no defects;
[0086] S101-12. Install the outer shell specimen in the fixture of the tensile testing machine, ensuring that the clamping position is firm and the two ends are symmetrical;
[0087] S101-13. Start the tensile testing machine and apply tensile force. During the stretching process, monitor and record the stress and strain changes of the outer shell; the loading rate is controlled between 1-5 mm / min;
[0088] S101-14. During the stretching process, record the breaking point of the outer shell; at this time, the test machine automatically stops and records the maximum tensile force and breaking strain;
[0089] S101-15. If the maximum tensile force of the outer shell specimen is higher than the tensile strength required by the design, the tensile test is qualified and the compression test is carried out in S101-2;
[0090] S101-16. If the maximum tensile force value of the outer shell specimen is lower than the tensile strength required by the design, the specimen is re-cut from the outer shell material away from the first cutting position, and the tensile test is re-performed. If the maximum tensile force value of the new outer shell specimen is higher than the tensile strength required by the design, the tensile test is qualified, and the compression test is performed in S101-2; if it is still lower than the tensile strength required by the design, the tensile test is unqualified, and the operator makes corresponding adjustments to the manufacturing method based on the test results;
[0091] S101-2, compression test:
[0092] S101-21. Cut a round or square specimen suitable for compression test from the same piece of outer shell material that has passed the outer shell tensile test. The size requirement is that the side length or diameter is 50mm and the thickness is 1.5 times the actual thickness of the outer shell. Ensure that the surface of the specimen is flat and free of defects;
[0093] S101-22. Place the specimen on the compression tester's lower platform, ensuring that the specimen is centered and stable;
[0094] S101-23. Apply compression force slowly, and control the compression rate at 1-2 mm / min. When the specimen begins to be subjected to pressure, record the applied compression force and the deformation of the specimen.
[0095] S101-24. Continue to apply the compressive force until the specimen begins to produce obvious permanent deformation or rupture, and record the maximum compressive force and its corresponding deformation;
[0096] S101-25. If the outer shell specimen does not break within the set load range and recovers well after compression, the compression test is qualified and the impact test is carried out in S101-3.
[0097] S101-26, if the outer shell specimen is broken within the set load range and has poor recovery after compression, the specimen is re-cut from the outer shell material away from the first cutting position, and the compression test is re-performed. If the new outer shell specimen does not break within the set load range and has good recovery after compression, the compression test is qualified, and the process goes to S101-3 for impact test; if it still breaks within the set load range and has poor recovery after compression, the compression test is unqualified, and the operator makes corresponding adjustments to the manufacturing method based on the test results;
[0098] S101-3, impact test:
[0099] S101-31. Cut standard-sized impact specimens from the same piece of outer shell material that has passed the outer shell tensile test and compression test. The size requirement is a square specimen of 10×10 cm. The surface of the specimen should be free of any cracks or defects to ensure the accuracy of the impact test;
[0100] S101-32. Fix the specimen on the support table of the impact tester to ensure its stable position;
[0101] S101-33. Start the impact tester and make the standard impact hammer hit the test piece at a set speed. Adjust the impact energy according to the design requirements.
[0102] S101-34. Record the cracks or damage of the test piece after impact and evaluate the impact resistance of the outer shell material;
[0103] S101-35. If the specimen has no cracks or breaks, the impact test is qualified;
[0104] S101-36. If cracks or ruptures occur on the specimen, the specimen shall be re-cut from the outer shell material away from the first cutting position and the impact test shall be re-performed. If the new outer shell specimen does not have cracks or ruptures, the impact test is qualified; if cracks or ruptures still occur, the impact test is unqualified and the operator shall make corresponding adjustments to the manufacturing method based on the test results;
[0105] The reliability and stability of the outer shell under various conditions such as tension, compression and impact are ensured. Through precise tension, compression and impact tests, the mechanical properties of the outer shell can be comprehensively evaluated, especially its performance under high-intensity loads. The tension test can test the tensile strength to ensure that the outer shell will not break or damage during the tension process, and ensure that it can withstand large tensile forces in actual use; the compression test tests the compressive strength of the outer shell, evaluates its deformation under the action of compression force, and ensures that the outer shell will not have excessive permanent deformation or rupture when subjected to external pressure; the impact test further verifies the impact resistance of the outer shell, ensuring that the outer shell can effectively absorb energy when encountering external impact and avoid damage to the vehicle body structure; through these strict quality controls, not only the high strength and impact resistance of the outer shell are ensured, but also the manufacturing method can be optimized to improve production efficiency, while reducing the waste and cost caused by unqualified products, ultimately making the manufacturing process more efficient.
[0106] In S2, the reinforcing material has a length of 10-15 mm and a diameter of 5-10 μm;
[0107] It helps to further optimize the strength and toughness of the outer shell, ensure that the reinforcement material can be evenly distributed inside the outer shell, and improve the mechanical properties of the material. When the length of the reinforcement material is controlled within the range of 10-15mm and the diameter is controlled within the range of 5-10μm, it can be effectively combined with the resin material to form a uniform reinforcement layer, avoiding the problem of unstable mechanical properties caused by the reinforcement material being too short or too thin. At the same time, a reasonable reinforcement material size can improve the tensile strength and impact resistance of the outer shell, further reduce the overall weight of the vehicle body, and achieve a lightweight design. This design not only improves the strength and toughness of the outer shell, but also reduces the production defect rate caused by uneven distribution or inappropriate size of the reinforcement material, thereby improving production efficiency and effectively reducing production costs. Overall, the design optimizes the performance and manufacturing process of the outer shell, making the outer shell of the scooter more in line with the market demand for high-strength, lightweight, and low-cost products. The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. The usual changes and substitutions made by technicians in this field within the scope of the technical solution of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for manufacturing an outer shell of a mobility scooter, characterized in that: The following steps are involved: S1. Preparation of outer shell substrate: First, according to the design requirements of the mobility scooter, select a suitable substrate: polypropylene or polyester or enhanced polyester material; and cut it into a predetermined outer shell mold shape; S2. Pretreatment of reinforcement materials: According to the strength requirements of the outer shell, select suitable reinforcement materials: glass fiber, carbon fiber or natural fiber; Pre-treating the prepared glass fiber, carbon fiber or natural fiber, using pickling and surface coating technology to make its surface have good adhesion properties and enhance the bonding strength with the resin material; the specific steps are: soaking the fiber material in a 5%-10% hydrochloric acid solution for 30 minutes, then washing with deionized water, and coating a layer of reinforcing agent after drying to ensure that the bonding strength between the resin and the fiber meets the preset requirements; S3. Preparation of reinforcing layer: The reinforcing layer is prepared by adding resin material: epoxy resin or polyurethane resin to the reinforcing material; this reinforcing layer is usually presented in the form of fabric or cloth, and has good mechanical properties and impact resistance; the formula used is: 50-60% epoxy resin, 30-40% glass fiber, 5-10% curing agent, and 5-10% solvent; S4. Mould design and preparation: Design and manufacture moulds that meet the requirements according to the shape and structure of the outer shell of the mobility scooter; The mold material is aluminum alloy to ensure good thermal conductivity and surface smoothness. The mold size and shape are optimized according to the vehicle body structure to ensure that the produced shell meets the various specifications of the vehicle body. S5. Preparation of a multi-layer composite structure: The reinforcement layer and the outer shell substrate are composited by a hot pressing process; at this time, an intermediate isolation layer can be added as needed to enhance the toughness, tensile strength and compressive strength of the outer shell; S6. Treatment of the exterior layer: In order to improve the appearance and durability of the outer shell of the mobility scooter, a layer of UV-resistant and corrosion-resistant exterior protective layer is applied to the outside of the composite structure; This protective layer can be coated with UV curing paint or polyurethane paint, and the thickness is generally controlled at 0.5-1mm; the formula of the paint used is: 60-70% polyurethane resin, 5-10% ultraviolet absorber, 10-15% curing agent, and 10-15% solvent; Through UV curing or heat curing, the exterior layer has good adhesion and weather resistance, ensuring that the surface of the outer shell of the mobility scooter can resist erosion by sunlight, rain and other environmental factors; S7. Reinforcement of the inner lining layer: In order to further improve the impact resistance and scratch resistance of the outer shell, a special inner lining layer can be coated inside the outer shell; the inner lining layer is generally made of high-strength polyurethane material, and the formula is: polyurethane resin 50-60%, nano filler 10-20%, curing agent 5-10%, solvent 10-15%; S8, curing treatment: put the treated outer shell into an oven for curing treatment; the curing temperature is 80℃-120℃, and the curing time is 12-16 hours to ensure full curing and make the outer shell have the best mechanical properties and thermal stability; S9, outer shell molding and trimming: The solidified outer shell is cooled, and the outer shell is initially molded; at this time, the outer shell needs to be fine-finished, polished and painted to ensure a smooth, defect-free and flawless appearance; during the trimming process, a fine grinding tool is used to polish the outer shell surface and trim the edge to ensure that the geometric size and shape of the outer shell meet the design requirements; S10, Testing and Quality Inspection: In order to ensure the quality of the outer shell of the mobility scooter, strict testing and quality inspection must be carried out. The testing contents include: S101, Strength test: Use tensile test, compression test and impact test methods to test the tensile strength, compressive strength and impact strength of the outer shell to ensure that it meets the use requirements; S102, temperature resistance test: put the outer shell into a high temperature environment for testing, to detect its tolerance under high temperature conditions, to ensure that it can still maintain stability under extreme temperature conditions; S103, corrosion resistance test: salt spray test and acid-base test are used to detect the corrosion resistance of the outer shell; S104, Appearance inspection: Conduct a comprehensive inspection on the outer shell surface to ensure there are no bubbles or cracks; S11. Finished product packaging and delivery: After passing the above tests, the outer shell will enter the packaging stage; according to customer needs, appropriate packaging treatment will be carried out to ensure that it is not damaged during transportation.
2. The method for manufacturing the outer shell of a mobility scooter according to claim 1, characterized in that: In S5, the specific compounding process includes: Preheating: Lay the base material and the reinforcement layer in the mold according to the predetermined direction and density, and preheat them. The temperature is controlled at 120℃-130℃ to achieve a better bonding effect during the subsequent compounding. Hot pressing: The heated substrate and reinforcement layer are hot pressed into shape. The molding process temperature is set at 150℃-180℃, the pressure is 8-12MPa, and the holding time is 20-30min to ensure that the composite layer is uniform and tight.
3. The method for manufacturing the outer shell of a mobility scooter according to claim 1, characterized in that: In S5, the middle isolation layer is composited by inorganic heat-insulating material and organic foam material, the mass ratio of the composite material is 60:40, and the thickness of the heat-insulating layer is 0.5 mm to 1 mm, ensuring that the outer shell has good heat-insulating performance.
4. The method for manufacturing the outer shell of a mobility scooter according to claim 1, characterized in that: In S101, the strength test includes the following steps: S101-1. Tensile test: S101-11. Cut a tensile test piece that meets the standards from the outer shell material; the test piece is usually in the shape of a long strip with a width of 20 mm and a thickness selected according to the actual thickness of the outer shell. The length is greater than 100 mm, and the surface of the test piece needs to be flat and smooth to ensure that there are no defects; S101-12. Install the outer shell specimen in the fixture of the tensile testing machine, ensuring that the clamping position is firm and the two ends are symmetrical; S101-13. Start the tensile testing machine and apply tensile force. During the stretching process, monitor and record the stress and strain changes of the outer shell; the loading rate is controlled between 1-5 mm / min; S101-14. During the stretching process, record the breaking point of the outer shell; at this time, the test machine automatically stops and records the maximum tensile force and breaking strain; S101-15. If the maximum tensile force of the outer shell specimen is higher than the tensile strength required by the design, the tensile test is qualified and the compression test is carried out in S101-2. S101-16. If the maximum tensile force value of the outer shell specimen is lower than the tensile strength required by the design, the specimen is re-cut from the outer shell material away from the first cutting position, and the tensile test is re-performed. If the maximum tensile force value of the new outer shell specimen is higher than the tensile strength required by the design, the tensile test is qualified, and the compression test is performed in S101-2; if it is still lower than the tensile strength required by the design, the tensile test is unqualified, and the operator makes corresponding adjustments to the manufacturing method based on the test results; S101-2, compression test: S101-21. Cut a round or square specimen suitable for compression test from the same piece of outer shell material that has passed the outer shell tensile test. The size requirement is that the side length or diameter is 50mm and the thickness is 1.5 times the actual thickness of the outer shell. Ensure that the surface of the specimen is flat and free of defects; S101-22. Place the specimen on the compression tester's lower platform, ensuring that the specimen is centered and stable; S101-23. Apply compression force slowly, and control the compression rate at 1-2 mm / min. When the specimen begins to be subjected to pressure, record the applied compression force and the deformation of the specimen. S101-24. Continue to apply the compressive force until the specimen begins to produce obvious permanent deformation or rupture, and record the maximum compressive force and its corresponding deformation; S101-25. If the outer shell specimen does not break within the set load range and recovers well after compression, the compression test is qualified and the impact test is carried out in S101-3. S101-26, if the outer shell specimen is broken within the set load range and has poor recovery after compression, the specimen is re-cut from the outer shell material away from the first cutting position, and the compression test is re-performed. If the new outer shell specimen does not break within the set load range and recovers well after compression, the compression test is qualified, and the process goes to S101-3 for impact test; if it still breaks within the set load range and has poor recovery after compression, the compression test is unqualified, and the operator makes corresponding adjustments to the manufacturing method based on the test results; S101-3, impact test: S101-31. Cut standard-sized impact specimens from the same piece of outer shell material that has passed the outer shell tensile test and compression test. The size requirement is a square specimen of 10×10 cm. The surface of the specimen should be free of any cracks or defects to ensure the accuracy of the impact test; S101-32. Fix the specimen on the support table of the impact tester to ensure its stable position; S101-33. Start the impact tester and make the standard impact hammer hit the test piece at a set speed. Adjust the impact energy according to the design requirements. S101-34. Record the cracks or damage of the test piece after impact and evaluate the impact resistance of the outer shell material; S101-35. If the specimen has no cracks or breaks, the impact test is qualified; S101-36. If cracks or breaks appear on the specimen, re-cut the specimen from the outer shell material away from the first cutting position and re-perform the impact test. If the new outer shell specimen does not have cracks or breaks, the impact test is qualified; if cracks or breaks still appear, the impact test is unqualified. The operator shall make corresponding adjustments to the manufacturing method based on the test results.
5. The method for manufacturing the outer shell of a mobility scooter according to claim 1, characterized in that: In S2, the reinforcing material has a length of 10-15 mm and a diameter of 5-10 μm.